Pengembangan Model Pembelajaran SAT Pada Manajemen Pemasaran - Evi Aulia Rachma; Ety Youhanita; Durrotun Nafisah (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2021)
This study aims to develop the SAT learning model in marketing management. The purpose of developing the SAT model is to help direct students' attention to focus more on understanding the material and improve student learning outcomes in accordance with learning objectives. Research on the development of the SAT learning model in the marketing management course will use the ADDIE development procedure to design the learning system. The trial design used was an empirical trial with a one-group pretest-posttest design model, in which there were two groups in the study, namely the control group and the experimental group. The results of the limited trial and the broad trial state that students responded with an average score of 85.56% and 86.75% for the attractiveness of the SAT learning model. Then the SAT learning model is effective when viewed from the posttest and pretest scores of students. The SAT learning model is efficient when viewed from the target time specified in the RPS.